Staff Training and Compensation Plan as Predictors of Teachers Job Performance in Public Secondary Schools, Lagos State - ODUNAYO, Henry Adewale (Ilorin Journal of Education, 2024)
This study assessed staff training and compensation plans as predictors of teachers’ job performance in Public Secondary Schools, in Lagos State. A descriptive research design type using a correlation approach was used as the design type seeks to investigate existing relationships. Three research hypotheses were designed for this study as public secondary school teachers in Lagos state form the population of the study. A sample size of one hundred and twenty (120) participants from six secondary schools in Epe and Ikeja LGAs was selected for this study through purposive and simple random sampling techniques. A self-designed instrument, Staff Training and Compensation Plan as Predictors of Teachers Job Performance Questionnaire (STCPPTJPQ) was used to generate data. The instrument was validated and index values of 0.871 and 0.804 were obtained through Cronbach alpha, a form of reliability which shows that internal consistency was met. Pearson Product Moment Correlation (PPMC) and Linear regression analysis were used to analyse the data and tested at a 0.05 significant level. From the results, all the hypotheses were rejected therefore showing the existence of a positive relationship between the independent and dependent variables. Moving forward one can conclude that staff training contributes the most to the prediction. Among others, the study concluded that to ensure better and improved teacher performance in our schools and institutions emphasis must be directed towards staff training as it remains one pivotal condition that can drive positive productivity.